Physiological Factors and Physical Activity Contribute to the Incidence of Type 2 Diabetes Mellitus in Indonesia - Simbolon, Demsa; Siregar, Afriyana; Talib, Ruzita ABD (UI Scholars Hub, 2020)
Type 2 diabetes mellitus (T2DM) is the sixth highest cause of death in Indonesia. Thus, it must be prevented and overcome with appropriate management. This study aimed to determine the contribution of physiological factors and physical activities to the incidence of T2DM. The study used a cohort retrospective design using secondary data from the Indonesian Family Life Survey (IFLS) from 2007 to 2014, which included a sample of 14,517 people involved for more than 20 years. Data analysis was performed using multiple logistic regressions. The results revealed a 3.8% incidence of T2DM in Indonesia. Record of hypertension risk increased the likelihood of T2DM by 1.7 times compared to without hypertension. A normal body mass index (BMI) increased the risk by 2.2 times, a higher BMI at 5.5 times, and BMI whose risk obesity was 7 times had greater likelihood of having T2DM compared with respondents with a thin BMI. After controlling for sex, age, marital status, record of parents’ DM, residence, employment, and education, results also indicated that people with less active physical activity were likely to have T2DM compared to those who were very active. Controlling blood pressure, maintaining a normal BMI, and increasing physical activity since adolescence can prevent T2DM.